A Kinect‐Based System for 3D Reconstruction of Sewer Manholes. (14th November 2014) - Bellés, Cristóbal; Pla*, Filiberto
Abstract A system for automatic 3D modeling of sewer manholes using two Microsoft Kinect sensors is presented. The hardware design is based on a hand‐held scanner that includes two Kinect sensors, a mini‐PC and LED‐based illumination bars. The scanning and reconstruction software has been implemented using open‐source software toolkits. The information from the two Kinect sensors is merged into a single 3D model. Reconstruction is performed by adapting an existing RGB‐D SLAM‐based algorithm by filtering out nonconsistent correspondences and an alternative graph‐based optimization, which results in reconstruction errors of the order of 1 cm. The final result obtained is a complete system with a hand‐held scanner and management software which is highly competitive with respect to present commercial systems, using much cheaper technology and open‐source toolkits with low reconstruction errors.